International network of cancer genome projects. - Hudson, T; Anderson, W; Artez, A; Barker, A; Bell, C; Bernabé, R; Bhan, M; Calvo, F; Eerola, I; Gerhard, D; Guttmacher, A; Guyer, M; et al. (2010)
The International Cancer Genome Consortium (ICGC) was launched to coordinate large-scale cancer genome studies in tumours from 50 different cancer types and/or subtypes that are of clinical and societal importance across the globe. Systematic studies of more than 25,000 cancer genomes at the genomic, epigenomic and transcriptomic levels will reveal the repertoire of oncogenic mutations, uncover traces of the mutagenic influences, define clinically relevant subtypes for prognosis and therapeutic management, and enable the development of new cancer therapies.